(untitled) (Swiss Medical Weekly, 2018)
INTRODUCTION Nowadays we typically use patient experience as a quality of care indicator, although this has some limitations. The aim of this study was to investigate to what extent patient, physician and practice characteristics were associated with patient-reported experience of care in the major dimensions in family medicine in a fee-for-service system. METHODS The data came from the Swiss part of the Quality and Costs of Primary Care (QUALICOPC) study, an international cross-sectional survey. A random sample of 194 Swiss family physicians and 1540 of their patients were included in this analysis. We assessed patient experience using three scores characterising access, communication and continuity-coordination. Multilevel statistical methods were used to analyse these scores based on patient-level, physician-level and practice-level factors. RESULTS Poor experience of access was associated with poor health (incidence rate ratio [IRR] 1.91, 95% confidence interval [CI] 1.54–2.55) but was lower among older patients (IRR 0.75, 95% CI 0.63–0.88). Experience of access was also reported as poorer in urban areas and in practices including other paramedical professionals (besides medical assistants) (IRR 1.27, 95% CI 1.06–1.51). Communication was reported as poorer in practices where physicians achieve greater daily face-to-face consultations (IRR 1.16, 95% CI 1.08–1.25) and in patients reporting higher incomes (IRR 1.24, 95% CI 1.01–1.52). Additionally, younger patients reported poorer continuity-coordination experience. In the continuity-coordination domain, patient experience appeared better in group practices (including other family physicians) and in those of physicians with a greater weekly workload in terms of hours. Finally, we found experience of communication and continuity better in the French-speaking area than German-speaking area of Switzerland. CONCLUSIONS In this study, we found that patient experience in family medicine in Switzerland was very good for all domains studied; access, family physician-patient communication and continuity-coordination of care. Most often, predictive factors of care experience relate to the patient’s characteristics, such as age and health status. However, several practice characteristics such as size, composition and functioning (in particular, time spent with the patient) represent potential levers for improving patient-reported experience. The variations observed between the three linguistic areas in Switzerland are also interesting, since they raise the issue of the role of sociocultural factors in this field.